Dose Distribution of Pencil Beam Proton Therapy using Geant4 Simulation for Breast Cancer Treatment - Budiman, Rizki; Sutanto, Heri; Tursinah, Rasito; Triadyaksa, Pandji (Diponegoro University Semarang Indonesia, 2025)
This study aims to obtain a Spread-Out Bragg Peak (SOBP) for breast cancer treatment using proton pencil beams Monte Carlo simulation. Proton beams with 2 MeV energy steps from 70 to 110 MeV were simulated using Geant 4 software to generate the SOBP. The optimization tool Linear Least Squares (lsqlin) was used to configure the proper proton beam weighting fraction. This tool successfully produced SOBPs within a depth range of 4-8 cm, 4-6 cm, and 5-7 cm. Comparison against a trial-and-error approach to creating SOBP by a different study shows that Linear Least Squares (lsqlin) approximation leads to a better SOBP.